2022
DOI: 10.1039/d1py01562a
|View full text |Cite
|
Sign up to set email alerts
|

RAFT aqueous dispersion polymerization of 4-hydroxybutyl acrylate: effect of end-group ionization on the formation and colloidal stability of sterically-stabilized diblock copolymer nanoparticles

Abstract: Poly(2-hydroxyethyl acrylate)-poly(4-hydroxybutyl acrylate) nano-objects are prepared by aqueous polymerization-induced self-assembly (PISA) using an ionic RAFT agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Variable temperature 1 H NMR studies indicated that the weakly hydrophobic HBA repeat units became more hydrated at elevated temperature. This is in striking contrast to the behavior observed for PHPMA-based diblock copolymers, where the HPMA repeat units become less hydrated on heating. ,,, Such contrasting behavior is rather counterintuitive given that HPMA and HBA are structural isomers. Unfortunately, the relatively low T g of the PHBA block led to film formation, which prevented the determination of copolymer morphologies via TEM .…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Variable temperature 1 H NMR studies indicated that the weakly hydrophobic HBA repeat units became more hydrated at elevated temperature. This is in striking contrast to the behavior observed for PHPMA-based diblock copolymers, where the HPMA repeat units become less hydrated on heating. ,,, Such contrasting behavior is rather counterintuitive given that HPMA and HBA are structural isomers. Unfortunately, the relatively low T g of the PHBA block led to film formation, which prevented the determination of copolymer morphologies via TEM .…”
Section: Introductionmentioning
confidence: 77%
“…However, direct comparison between the PEG 45 –PHBMA 20 worms reported herein and the previously reported PEG 113 –PHPMA 220 worms is somewhat problematic given the different PEG stabilizer block DPs. Furthermore, a much lower PHBMA DP is required to access the worm phase because this core-forming block is significantly more hydrophobic than either PHBA ,, or PHPMA. , Heating the PEG 45 –PHBMA 20 dispersion above 58 °C resulted in a substantial reduction in viscosity, suggesting a worm-to-vesicle transition. , Heating to 75 °C led to a second, smaller increase in viscosity, which corresponds to the formation of lamellae (see Figure d) . These thermal transitions proved to be remarkably reversible, with relatively little hysteresis being observed at heating/cooling rates of 1 °C min –1 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, with the benefit of hindsight, this RAFT agent is mainly present in its anionic carboxylate form under the reaction conditions summarized in Scheme (i.e., at pH 5.5). According to the aqueous PISA literature, such terminal anionic charge can enhance the colloidal stability of the final diblock copolymer nanoparticles via an electrosteric stabilization mechanism. ,, Moreover, literature precedent suggests that a higher chain extension efficiency and a lower final dispersity are usually obtained when employing a one-pot synthesis protocol, rather than when utilizing a purified water-soluble precursor (e.g., PHEAC 216 in the present study). Accordingly, we decided to explore the feasibility of conducting the one-pot synthesis of PHEAC 220 -PNAM 6000 diblock copolymer particles using a non-ionic RAFT agent (MeBDMAT) under the reaction conditions shown in Scheme . The initial synthesis of the PHEAC 220 precursor was conducted at 70% w/w solids to enable the HEAC monomer to act as a cosolvent for the otherwise water-insoluble MeBDMAT reagent.…”
Section: Resultsmentioning
confidence: 98%